DYSLEXIA AND THE CHALLENGES IN LITERACY: AN INTEGRATIVE LITERATURE REVIEW - Santana, Caroline Alvarenga de Assis; Oliveira, Ana Clara da Silva; Alves, Aline Míriam Cunha (Seven Editora, 2025)
Dyslexia is a learning disorder of neurological origin, characterized by difficulty in decoding and spelling words. It is one of the learning disorders that affects writing and reading and consequently interferes with the literacy process. The objective of this study was to understand how the literacy process occurs in children with dyslexia. This is a literature review conducted using the electronic databases Capes, PubMed/Medline, Scielo, and BVS, considering the last 15 years. The descriptors used for the search were: Dyslexia, literacy, inclusion, interventions, assistive technology, educational strategies, and teaching practice. Sixteen articles addressing the literacy process of dyslexic children were selected. It was observed that the literacy of dyslexic children depends not only on the literacy process itself, but also on the child, the teacher, the methodology, the parents, and, above all, environmental influences. Dyslexia makes the literacy process even more complex, requiring a review of pedagogical practices to ensure a more inclusive and high-quality education for all.DOI: https://doi.org/10.56238/sevened2025.038-076